Fuzzy Delphi Method Application in Developing Methodology for Integrating Memorised Quranic Verses with Aqli Knowledge Based on Quranic Exegesis - Ahmad Bazli Ahmad Hilmi; Muhammad Hafiz Saleh; Adibah Sulaiman; Selamat bin Amir (Brill, 2024)
This is a postprint article. Indexed by WOS